Embryo-secreted microRNAs enable non-invasive assessment of chromosomal status and viability in in vitro fertilization - Esmaeilivand, Masoumeh; Nasr-Esfahani, Mohammad Hossein (Frontiers in Cell and Developmental Biology, 2026)
Selecting embryos with the highest developmental potential remains a decisive step for achieving successful in vitro fertilization outcomes. Conventional evaluation methods such as morphological grading, time-lapse imaging, and preimplantation genetic testing for aneuploidy provide valuable information but are limited by subjectivity, invasiveness, and cost. These challenges have driven increasing interest in non-invasive biomarkers capable of improving the precision and safety of embryo assessment. Emerging evidence indicates that human embryos actively release microRNAs into their surrounding environment, particularly into the spent culture medium and blastocoel fluid. These extracellular microRNAs regulate pathways involved in cell cycle progression, apoptosis, differentiation, and embryo-endometrium communication. Distinct expression signatures, including miR-21-5p, miR-661, and members of the miR-17∼92 cluster, correlate with chromosomal integrity and implantation competence, suggesting their potential as complementary or alternative biomarkers to trophectoderm biopsy. Comparative analyses across digital PCR, quantitative RT-PCR, microarray, and next-generation sequencing platforms reveal both methodological advances and unresolved challenges, such as low RNA yield, contamination risk, and inconsistent normalization strategies. Embryo-derived microRNAs thus represent a promising avenue for non-invasive embryo evaluation, with future clinical translation hinging on robust multicenter validation and integration with imaging, metabolomics, and artificial intelligence–based analytics.